1997
DOI: 10.1038/sj.onc.1200983
|View full text |Cite
|
Sign up to set email alerts
|

Activation of FGF receptors by mutations in the transmembrane domain

Abstract: Signaling through FGF receptors, which constitute a family of membrane-spanning tyrosine kinases, can stimulate cell proliferation, induce or inhibit cell di erentiation and plays an important role in development. Recently, mutations in FGF receptors have been shown to be associated with a number of genetically dominant human skeletal disorders. A remarkably conserved mutation (Gly 380?Arg) in the transmembrane region of FGFR-3 has been shown to be responsible for achondroplasia (ACH) but it was not clear whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 26 publications
3
57
0
Order By: Relevance
“…Our data indicate that deregulated FGFR3 mutants in KMS-11 and OPM-2 cells are phosphorylated under serum-deprived conditions, thus con®rming that these two mutations are capable of inducing constitutive receptor activation as has been observed in various cell types transfected with FGFR3 constructs (Naski et al, 1996;Webster et al, 1996;Webster and Donoghue, 1997b;Li et al, 1997). These data are supported by our analysis of U266 transfected cells expressing wildtype or Y373C FGFR3, which showed that only the mutated receptor is phosphorylated in the absence of the ligand.…”
Section: Discussionmentioning
confidence: 87%
“…Our data indicate that deregulated FGFR3 mutants in KMS-11 and OPM-2 cells are phosphorylated under serum-deprived conditions, thus con®rming that these two mutations are capable of inducing constitutive receptor activation as has been observed in various cell types transfected with FGFR3 constructs (Naski et al, 1996;Webster et al, 1996;Webster and Donoghue, 1997b;Li et al, 1997). These data are supported by our analysis of U266 transfected cells expressing wildtype or Y373C FGFR3, which showed that only the mutated receptor is phosphorylated in the absence of the ligand.…”
Section: Discussionmentioning
confidence: 87%
“…The activated receptor has a cysteine to arginine mutation at position 382 in the transmembrane domain. We have previously shown that this receptor is capable of transforming NIH3T3 cells and is tyrosine-phosphorylated even in the absence of ligand (Li et al, 1997). Several clones were isolated and those expressing the highest levels of FGFR-2/ C382R were selected for further study.…”
Section: Expression Of Fgfs and Fgf Receptors In Breast Cancer Cellsmentioning
confidence: 99%
“…Expression of Bek 2.0 kb considerably decreased the FGFinhibition of CAT activity in the MCF-7 cells. Expression of a construct encoding the wild type FGFR-2 reduced overall CAT activity, presumably due to receptor activation resulting from high levels of expression (Li et al, 1997), but FGF-mediated inhibition of the estrogen response was still detectable. Cotransfection with a plasmid encoding the activated FGFR-2/C382R strikingly reduced the activity even further although estrogen-inducibility was still maintained.…”
Section: E Ect Of Fgf On Estrogen-induced Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mutation activates FGFR3 in the absence of ligand. However, the mutant receptor is further activated in the presence of ligand (Naski et al 1996;Webster and Donoghue 1996;Li et al 1997). Two different substitution mutations account for most cases of TD.…”
Section: Chondrodysplasia Syndromes and Mutations In Fgfr3mentioning
confidence: 99%